Effects of Motivational Group Therapy Counseling on Perceived Self-Efficacy and Smoking Cessation among Patients with Substance-Induced Psychotic Disorders - Sanitwong Na Ayuttaya, Khwanruean; Phuphet, Kedsirin; Tejavanija, Naiyanan; Sanitwong Na Ayuttaya2, Saksit (Princess of Naradhiwas University Journal, 2025)
The quasi-experimental research aimed to compare the score levels of perceived self-efficacy in quitting smoking and the proportion of smokers who quit between the experimental group and the control group. Sample groups were 30 patients with substance use and concomitant smoking addiction, matched individually (matched subjects) into control and experimental groups, with 15 patients in each group. The control group received standard care, while the experimental group received standard care along with motivational group therapy counseling for smoking cessation. The research instruments that were used included 1) motivational group therapy counseling for smoking cessation, 2) a general information questionnaire, 3) the self-efficacy assessment for quitting smoking, which had a content validity index of 0.67-1.00 and a Cronbach’s alpha coefficient of 0.84, and 4) the questionnaire on smoking cessation. Data were analyzed using descriptive statistics, and the data were compared using paired t-test statistics, independent t-test statistics, and Fisher’s exact test statistics. Research findings indicated that the experimental group had significantly higher average scores of self-efficacy in quitting smoking after receiving motivational group therapy counseling compared to the control group (p <.05). When comparing within the experimental group, the average score of self-efficacy in quitting smoking after receiving the intervention was significantly higher than before receiving it (p<.001). Additionally, after a 1-month follow-up, the proportion of patients who quit smoking in the experimental group was significantly higher than in the control group (p<.05).